(untitled) (Research, Society and Development, 2025)
The objective of this scoping review is to map the competencies required of clinical supervisors of nursing students. A scoping review will be conducted following Joanna Briggs Institute guidelines and the PRISMA-ScR checklist. We will search PubMed, CINAHL, PsycINFO, Scopus, and Web of Science, as well as grey literature sources, covering from 1993 through July 2025 without language restrictions. Inclusion criteria comprise studies involving clinical supervisors of undergraduate and postgraduate nursing students (Participants), explicitly defining the knowledge, skills, and attitudes that constitute effective supervision (Concept) in clinical education settings, such as hospital wards, community health settings, and simulation laboratories (Context). Two independent reviewers will screen titles/abstracts and full texts using Rayyan, with disagreements resolved by a third reviewer. Data charting will employ a piloted extraction form. The results of the search will be presented in a PRISMA-ScR flow diagram. Findings will be reported via narrative synthesis and tabular summaries detailing author/year, study aim, methodological design, competency definitions (knowledge, skills, attitudes), application contexts, and key conclusions. This comprehensive competency mapping is expected to inform educational practice, guide future research and underscore the importance of clinical supervision in nursing student training, curriculum development, and professional development.